Roti nan (Nan.Co) / Muhammad Faruq Muizuddin ... [et al.] - Muhammad Faruq, Muizuddin; Mohammad Nur Amirullah, Shahrul Nizam; Amir Aiman Aniq, Ahmad Rashidi; Norsalinda, Tan Sali; Nor Syazwana Firhana, Shariff (2019)
This business plan is about the plan before conducting a business named as Nan.Co Cafe. Our company has been named as Nan.Co Cafe. The name of the company is Nan.Co Cafe which was inspired by Nan Cheese restaurant at Chenderiang. The company is being established on 30th September 2019. The partners of the business in the company stand with 5 people. The business will be commencing in the 1st February 2020 at AEON Shopping Mall Shah Alam. The purpose of the business is to evaluate the project viability and growth potential, to act as a guideline for the management of the proposed business, to allocate business resources effectively. The main activity of the business is cafe and food services. Food and drinks will be serving, and the main food is Nan Cheese while the drink is random. The business will be started with the accumulate budget is about RM60,480.00 for this business. In this business plan consist of some plans which are marketing plan, operational plan, administration plan, and financial plan. Every plan has their owned budget that has been list out in this business plan proposal. For the operational plan, the budget that will be going to use is about RM40,720.00. Otherwise, RM4339.00 is the budget that marketing plan going to use in the business. Besides, for the administrative budget, only spend about RM53,666.00 for fixed assets and other expenses while monthly expensesare only spending for RM8033.00. Next, the financial Plan going to show either the business will experience of loss or experience with gain of profits. According to the financial report, the business will be going to gain profits in every month and the amount of money in higher than money out.